Х - трехколесных
(7-х) - двухколесных
3х + 2*(7-х) = 18
3х-2х+14=18
х=18-14=4 трехколес
7-4=3 двухколес
2 log10 (x+1)= log10 (2x+5)
(X+1)^2=(2x+5)
X^2+2x+1-2x-5=0
X^2-4=0
X^2=4
X=2
2 т 886 кг= 2886 кг
7 т 795 кг= 7795 кг
2886+7795= 10681
10681 кг= 10 т 681 кг
74-7=(60+14)-7=60+(14-7)=60+7=67
52-8=(40+12)-8=40+(12-8)=40+4=44
85-6=(70+15)-6=70+(15-6)=70+9=79
85-9=(70+15)-9=70+(15-9)=70+6=76
52-9=(40+12)-9=40+(12-9)=40+3=43
74-6=(60+14)-6=60+(14-6)=60+8=68
85-7=(70+15)-7=70+(15-7)=70+8=78
85-8=(70+15)-8=70+(15-8)=70+7=77